2021
DOI: 10.3390/agronomy11081651
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium transporter Gene Family: Genome-Wide Identification and Characterization in Theobroma cacao, Corchorus capsularis, and Gossypium hirsutum of Family Malvaceae

Abstract: Magnesium (Mg) is an element involved in various key cellular processes in plants. Mg transporter (MGT) genes play an important role in magnesium distribution and ionic balance maintenance. Here, MGT family members were identified and characterized in three species of the plant family Malvaceae, Theobroma cacao, Corchorus capsularis, and Gossypium hirsutum, to improve our understanding of their structure, regulatory systems, functions, and possible interactions. We identified 18, 41, and 16 putative non-redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 87 publications
0
34
0
Order By: Relevance
“…3 C and 4 A). Those high variation in the sequence structure revealed that TIFY family members have acquired changes in their genome during evolution events that affected their functions [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 C and 4 A). Those high variation in the sequence structure revealed that TIFY family members have acquired changes in their genome during evolution events that affected their functions [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physiological data about hormones and plant growth promotion, we further analyzed the data at the molecular level by transcriptomic analysis experiment by using two kinds of samples, 100 ppm IBA-treated buds (T) and control buds (CK). In recent times, modern biotechnological, bioinformatics tools and big-data platforms have helped understand the functions of genes and gene families up to depth ( Hoang et al, 2017 ; Abdullah et al, 2021 ; Faraji et al, 2021 ; Heidari et al, 2021 ; Manechini et al, 2021 ). In this study, RNA-seq results revealed that The IBA treatment significantly influenced DEGs regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium (Mg) is a vital element for living cells involved in many critical cellular activities [1][2][3]. For instance, Mg as a cofactor is essential for the activity of many enzymes (> 300 enzymes) such as kinase, polymerase, and H + -ATPase [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on sequence structure, MGTs have been classified into three groups, including MRS2, CorA, and NIPA [10]. MRS2 and CorA proteins are recognized by a tripeptide conserved region, GMN (Glycine-Methionine-Asparagine), and two or three transmembrane (TM) domains in their C-terminal ends [11], while NIPAs contain several TMs in its structure [3,10]. However, our knowledge of NIPA class is limited.…”
Section: Introductionmentioning
confidence: 99%